Bastard Culture! How User Participation Transforms Cultural Production - Schäfer, M.T (MediaMatters, 2011)
New online technologies have brought with them a great promise of freedom. The computer and particularly the Internet have been represented as enabling technologies, turning consumers into users and users into producers. Furthermore, lay people and amateurs have been enthusiastically greeted as heroes of the digital era. This thoughtful study casts a fresh light on the shaping of user participation in the context of, among others, popular discourse in and around new media. Schäfer's groundbreaking research into hacking, fan communities and Web 2.0 applications demonstrates how the dynamic of innovation, control and interaction have shifted the boundaries of the traditional culture industry into the user domain. The media industry undergoes a shift from creating content to providing platforms for user driven social interactions and user-generated content. In this extended culture industry, participation unfolds not only in the co-creation of media content and software-based products, but also in the development and defense of distinctive media practices that represent a socio-political understanding of new technologies.